In Situ XOR Encryption for Lightweight Security Using Nanoelectromechanical Physically Unclonable Functions - Changha Kim; Jin Wook Lee; Geun Tae Park; Myeong Su Shin; Seung Hun Baek; Jae Seung Woo; Woo Young Choi (Advanced Intelligent Systems)
An in situ XOR encryption/decryption approach using a nanoelectromechanical physically unclonable function (NEM‐PUF) is proposed for the first time. It addresses the critical security issues during data transfer between servers/clouds and resource‐constrained edge devices. The monolithic integration of NEM‐PUFs using the complementary metal–oxide–semiconductor (CMOS) back‐end‐of‐line (BEOL) process leverages process‐induced intentional random stiction as an entropy source. The unique ability of NEM‐PUF cells to store complementary data within a single cell enables bitwise in situ XOR operations. This feature of NEM‐PUF‐based in situ XOR encryption eliminates the need for complex cryptographic algorithms, which significantly reduces the power consumption, footprint, and latency compared with conventional cryptography schemes. The proposed in situ XOR encryption is demonstrated effectively within a typical federated learning domain, showcasing its broad potential applications for Internet of Things security.